Regime shifts in perspective - The North Sea and Atlantic cod (Gadus morhua) as paradigmatic examples - Blöcker, Alexandra Michelle (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2022)
Marine ecosystems are heavily impacted by anthropogenic stressors, in particular fish stocks worldwide are overexploited. Policies were implemented to reduce fishing pressure and to aim for fish stock recovery to sustain impacted socio-ecological systems, with limited success. Recovery can be hindered by so-called regime shifts, where a system can no longer withstand the pressure of certain drivers, loses stability in structure and functioning, and abruptly shifts to another system state. Transforming back to a former state can be hampered by hysteresis and irreversibility. The North Sea and Atlantic cod (Gadus morhua) are paradigmatic examples for regime shifts. Both have been affected by regime shifts, with North Sea cod remaining in a depleted state. A common understanding among stakeholders about the regime shift concept, underlying driving forces, and consequences of these shifts are of high importance, as a foundation for sustainable management measures to avoid marine resource depletion. This thesis focuses on the framing of the regime shift concept among stakeholders involved with Atlantic cod and regime shifts in the North Sea, as well as the detection of regime shifts in the North Sea fish community, with a particular focus on Atlantic cod. I used qualitative and quantitative methods to analyze the perception of different stakeholders on regime shifts and to determine underlying regime shift drivers as well as recovery potential of fish stocks. Due to changes in structures and functioning, regime shifts have strong implications for the socio-ecological system. The findings in this thesis highlight that an adaptive ecosystem-based management approach is required to successfully manage fish stocks in the North Sea. A common understanding of the regime shift concept among stakeholders is essential to support communication and enhance the acceptance of management measures. Including stakeholders in decision-making and incorporating regime shift dynamics in fisheries management can help decision-makers to ...